The Use of Body Part Names in Uzbek Language Metaphors - Tokareva Ekaterina Borisovna (Zien Journals, 2022)
This article is devoted to the actual linguistic problem, the problem of using the names of body parts in the Uzbek language. The paper defines the basic concepts, and also emphasizes the reasons for the metaphorization of the language. In fact, the article explores some metaphorical units of the Uzbek language, which are firmly entrenched in the thinking space.
Keywords: names of body parts; aesthetic potential; form of thinking; metaphor